Simultaneous determination of bisoprolol fumarate and rosuvastatin calcium in a new combined formulation by validated RP-HPLC - Zaki, Marco Mounir; Abdelwahab, Nada Sayed; Ali, Adel Ahmed; Sharkawi, Souty Mounie Zaki (European Journal of Chemistry, 2019)
A simple, specific, and precise RP-HPLC method was developed and validated for simultaneous determination of Bisoprolol fumarate (BIS) and Rosuvastatin calcium (ROS) in new formulated tablets. The developed RP-HPLC method depended on chromatographic separation using C18 column (150×4.6 mm, 0.5 μm) with mobile phase consisted of acetonitrile and 0.05 aqueous solution of orthophosphoric acid at the ratio of 65:35 % (v:v) with a flow rate of 1 mL/min and UV detection was carried out at 230 nm. Factors affecting the developed methods were studied and optimized and the retention times for BIS and ROS were found to be 2.758 and 4.974 min, respectively. Linearity of the proposed method was observed over a concentration range 0.2-50 μg/mL for each of BIS (r = 0.9999) and ROS (r = 0.9998). The proposed method was successfully applied for the determination of the studied drugs in their bulk powder, laboratory prepared mixtures and in the formulated tablets. The developed method is the first chromatographic method for determination of those drugs and showed no significant difference when compared with the reported methods.